Localised systems in relativistic quantum information - Lee, Antony Richard (2013)
This thesis collects my own and collaborative work I have been involved with finding localised systems in quantum field theory that are be useful for quantum information. It draws from many well established physical theories such as quantum field theory in curved spacetimes, quantum optics and Gaussian state quantum information. The results are split between three chapters.